2021
DOI: 10.3390/nu13051465
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Weight Loss by Low-Calorie Diet on Cardiovascular Health in Type 2 Diabetes: An Interventional Cohort Study

Abstract: Cardiovascular disease (CVD) remains a major problem for people with type 2 diabetes (T2DM), and the leading cause of death worldwide. We aimed to determine cardiovascular benefits of weight loss with or without remission of diabetes, and to assess utility of plasma biomarkers. 29 people with T2DM were studied at baseline and after dietary weight loss. Change in plasma adipokines and lipid related markers was examined in relation to weight loss, diabetes remission, 10-year cardiovascular risk (QRISK), and dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
8
0
1
Order By: Relevance
“…Despite substantial weight loss of 7.3 kg on average and concomitant health improvements [ 32 ], 12 weeks of 25% energy reduction did not affect fasting FGF21 levels. Previous weight loss trials have reported conflicting findings, with some trials reporting a reduction in fasting FGF21 levels upon diet-induced weight loss [ 9 , 10 , 11 , 12 , 13 ], and others reporting an increase [ 40 ] or no effect on circulating FGF21 levels [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Generally, the studies that report a change in plasma fasting FGF21 were performed in individuals with more severely impaired metabolic health (e.g., T2DM, NAFLD, morbid obesity), who typically have elevated FGF21 levels and thus more room for improvement compared to individuals in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite substantial weight loss of 7.3 kg on average and concomitant health improvements [ 32 ], 12 weeks of 25% energy reduction did not affect fasting FGF21 levels. Previous weight loss trials have reported conflicting findings, with some trials reporting a reduction in fasting FGF21 levels upon diet-induced weight loss [ 9 , 10 , 11 , 12 , 13 ], and others reporting an increase [ 40 ] or no effect on circulating FGF21 levels [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Generally, the studies that report a change in plasma fasting FGF21 were performed in individuals with more severely impaired metabolic health (e.g., T2DM, NAFLD, morbid obesity), who typically have elevated FGF21 levels and thus more room for improvement compared to individuals in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, circulating FGF21 levels have been reported to positively associate with BMI, body fat, liver fat content, blood pressure, insulin resistance (IR) and atherogenic lipid profiles [ 5 , 6 ], as well as predict incident metabolic syndrome and T2DM [ 7 , 8 ]. It is unclear whether and how weight loss and accompanying health improvements affect FGF21 levels, with some trials reporting reduced levels of circulating FGF21 upon diet-induced weight loss [ 9 , 10 , 11 , 12 , 13 ], and others reporting no effects on FGF21 [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Weight loss brought about similar changes in intraorgan fat and VLDL1-TG production rate but not fasting plasma VLDL1-TG levels in both sexes. Estimated CVD risk was high in diabetes, with substantial improvement in both sexes after weight loss [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among all the factors that could affect the CRIWL-induced cFGF21 change, we found that the protein content in the diet could be a key factor with a 30% calorie from protein as a cutoff value. Most of the CRIWLdecreased cFGF21 results were obtained with relatively high dietary protein contents (≥30E% protein) (32)(33)(34)(35)(36), while controversial results were obtained with relatively low dietary protein contents (<30E% protein) (36)(37)(38)(39)(40) or with diets with unspecified protein contents (32,41,42).…”
Section: Calorie Restriction-induced Weight Loss and Cfgf21mentioning
confidence: 99%